Homework Help

Simplify: `(-x^2*y^2)/(x^(1/2)*y^0)`

user profile pic

soffeelulu | eNoter

Posted April 29, 2013 at 5:39 PM via iOS

dislike 3 like

Simplify: `(-x^2*y^2)/(x^(1/2)*y^0)`

2 Answers | Add Yours

user profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted April 29, 2013 at 5:45 PM (Answer #1)

dislike 2 like

The expression `(-x^2*y^2)/(x^(1/2)*y^0)` has to be simplified.

`(-x^2*y^2)/(x^(1/2)*y^0)`

= `(-x^2*y^2)/(x^(1/2)*1)`

= `-x^(2-1/2)*y^2`

= `-x^(3/2)*y^2`

The simplified form of `(-x^2*y^2)/(x^(1/2)*y^0) = -x^(3/2)*y^2`

user profile pic

oldnick | Valedictorian

Posted April 30, 2013 at 12:14 AM (Answer #2)

dislike 0 like

`-(x^2y^2)/(x^(1/2)y^0)=` `-x^(2-1/2)y^(2-0)=-x^(3/2)y^2=-xy^2sqrt(x)`

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes